Strength and balance asymmetries in children and adolescents: comparison between single- and multi-sport participants - Wilczynski, B.; Buler, J.; Buler, R. I.; Grochowski, M. I.; Puchalski, B.; Zorena, K. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Prior research has suggested links between youth sport special-ization, inter-limb asymmetries, and injury risk, but findings remain inconsistent regarding whether single-sport athletes show greater asymmetries than their multi-sport peers. This study examined differences in inter-limb asymme-try (global, balance, strength) between single- and multi-sport athletes, and explored the prevalence of exceeding clinical thresholds, sex- and sport-specific interactions, and associations with training volume and injury history.